Habitat Approach for Conservation of Herbs, Shrubs and Climbers in the Shara Vathi River Basin - Rao, G. R.; Subhashchandran, M. D.; Ramachandra, T. V. (Indian Forester, 2005)
Sharavathi river basin (upper catchment) falls in one of the megacentres of endemism (Shimoga-Kanara) harbouring diverse kinds of flora and fauna, which are adapted to various kinds of habitats. Study was carried out to know the habitat preferences of the endemic species particularly of herhs, shrubs, orchids, and climbers excluding the trees. Field survey covered 21 micro- and macro-habitats and the results show that the macrohabitats (such as grasslands, evergreen-semi evergreen forests and marshy areas) have higher species richness and endemism. To prioritise habitats for conservation, micro and macro habitats were ranked according to their richness in species and endemism. The result reveals that grasslands, evergreen-semi evergreen forests and marshy areas deserve higher conservation priorities. Micro-habitats such as wet tree trunks, wet-rocks etc., have distinctive species very much different from other habitats. All these habitats also harboured economically useful species including medicinal plants vital for human survival.